Holistic education in the perspective of ibn khaldun: The relevance of the concepts of tadrīj, takrīr, and asabiyyah - Fauzan Nur Fahmi; Ahmad Sukandar (At Turots: Jurnal Pendidikan Islam, 2025)
This study critically examines the educational philosophy of Ibn Khaldun and its significance for the development of Islamic Religious Education (PAI) in contemporary contexts. The research addresses the limited scholarly attention to Ibn Khaldun’s specific contributions to curriculum and pedagogy, despite their enduring relevance. Using a qualitative library research approach, the study analyzes Muqaddimah as the primary source, supported by secondary literature, and applies thematic content analysis within a socio-historical framework. The findings demonstrate that Ibn Khaldun formulated a holistic educational model integrating transmitted (naqli) and rational (‘aqli) knowledge, emphasized the methods of tadrīj (gradual learning) and takrīr (repetition) aligned with modern cognitive psychology, and viewed education as a means to strengthen asabiyyah (social solidarity). These concepts not only describe and explain educational phenomena but also provide predictive insights applicable to twenty-first-century pedagogy. The study concludes that Ibn Khaldun’s philosophy offers an integrative model that can inform curriculum innovation, character education, and the renewal of Islamic pedagogy in the modern era.